2009
DOI: 10.1073/pnas.0904740106
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics and economics of rabies control in dogs and humans in an African city

Abstract: Human rabies in developing countries can be prevented through interventions directed at dogs. Potential cost-savings for the public health sector of interventions aimed at animal-host reservoirs should be assessed. Available deterministic models of rabies transmission between dogs were extended to include dog-to-human rabies transmission. Model parameters were fitted to routine weekly rabid-dog and exposed-human cases reported in N Djamé na, the capital of Chad. The estimated transmission rates between dogs (␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
285
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(307 citation statements)
references
References 15 publications
8
285
1
3
Order By: Relevance
“…Since no wildlife rabies cases have been reported in Bhutan, it can be concluded that rabies in cattle or in other domestic animals is due to rabies in dogs. In developing countries, including Bhutan, the domestic dog is the main source of exposure and a primary vector for human rabies and other domestic livestock (Knobel et al, 2005;Zinsstag et al, 2009;Tenzin and Ward, 2012b). Therefore, rabies cases in cattle were used as proxy for the dog rabies problem in Bhutan since the reporting of rabies cases in cattle is more sensitive, reliable and timely than that of dog reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Since no wildlife rabies cases have been reported in Bhutan, it can be concluded that rabies in cattle or in other domestic animals is due to rabies in dogs. In developing countries, including Bhutan, the domestic dog is the main source of exposure and a primary vector for human rabies and other domestic livestock (Knobel et al, 2005;Zinsstag et al, 2009;Tenzin and Ward, 2012b). Therefore, rabies cases in cattle were used as proxy for the dog rabies problem in Bhutan since the reporting of rabies cases in cattle is more sensitive, reliable and timely than that of dog reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on both field data and previous modelling [2,3,16,17], we included three model parameters that together determine mortality rates of dogs and wildlife, respectively: a frequencydependent term, a density-dependent term, and rabies-related mortality. The frequency-dependent term, m, was included as a constant rate of removal from each compartment to represent adult canine mortality in Tanzania.…”
Section: (B) Model Structurementioning
confidence: 99%
“…Previous analyses have been based on relatively closed systems [2,3,7], ignoring the possible impact of rabies reintroduction from unvaccinated regions. However, rabies virus transmission across national and sub-national borders has been documented in Sub-Saharan Africa [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations